Surface-Modified Multifunctional Thymol-Loaded Biodegradable Nanoparticles for Topical Acne Treatment - Camila Folle; Natalia Díaz-Garrido; Elena Sánchez-López; Ana Maria Marqués; Josefa Badia; Laura Baldomà; Marta Espina; Ana Cristina Calpena; María Luisa García (MDPI AG, 2021)
The present work is focused on the development of novel surface-functionalized poly(lactic-co-glycolic acid) nanoparticles loaded with thymol (TH-NPs) for topical administration enhancing thymol anti-inflammatory, antioxidant and wound healing activities against acne. TH-NPs were prepared by solvent evaporation method using different surface functionalization strategies and obtaining suitable physicochemical parameters and a good short-term stability at 4 °C. Moreover, TH-NPs skin penetration and antioxidant activity were assessed in ex vivo pig skin models. Skin penetration of TH-NPs followed the follicular route, independently of the surface charge and they were able to enhance antioxidant capacity. Furthermore, antimicrobial activity against Cutibacterium acnes was evaluated in vitro by the suspension test showing improved antibacterial performance. Using human keratinocyte cells (HaCat), cytotoxicity, cellular uptake, antioxidant, anti-inflammatory and wound healing activities were studied. TH-NPs were non-toxic and efficiently internalized inside the cells. In addition, TH-NPs displayed significant anti-inflammatory, antioxidant and wound healing activities, which were highly influenced by TH-NPs surface modifications. Moreover, a synergic activity between TH-NPs and their surface functionalization was demonstrated. To conclude, surface-modified TH-NPs had proven to be suitable to be used as anti-inflammatory, antioxidant and wound healing agents, constituting a promising therapy for treating acne infection and associated inflammation.